The Differentiation and Maintenance of SARS-CoV-2-Specific Follicular Helper T Cells - Wang, Yifei; Tian, Qin; Ye, Lilin (Frontiers in Cellular and Infection Microbiology, 2022)
Upon acute viral infection, virus-specific CD4+ T cells differentiate into either TH1 cells or follicular helper T (TFH) cells. The molecular pathways governing such bimodal cell fate commitment remain elusive. Additionally, effector virus-specific TFH cells further differentiate into corresponding memory population, which confer long-term protection against re-infection of same viruses by providing immediate help to virus-specific memory B cells. Currently, the molecular mechanisms underlying the long-term maintenance of memory TFH cells are largely unknown. In this review, we discuss current understanding of early differentiation of virus-specific effector TFH cells and long-term maintenance of virus-specific memory TFH cells in mouse models of viral infection and patients of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection.